Kemampuan Berpikir Kausalitas dalam Pembelajaran Sejarah dan Implikasinya terhadap Pendidikan Berkualitas - Krismawarni Krismawarni; Akhmad Arif Musadad; Musa Pelu (Universitas Hamzanwadi, 2026)
Quality education is a key pillar in achieving the Sustainable Development Goals (SDGs), particularly SDG 4, which emphasizes mastery of 21st-century competencies, such as critical thinking and causal reasoning. History learning plays a strategic role in the context of quality education because it is based on the concept of historical thinking skills, where causal thinking skills are a core component. However, history learning practices are often oriented towards memorizing facts and do not encourage an understanding of complex cause-and-effect relationships. This study aims to analyze and synthesize literature related to the role of history learning in developing causal thinking skills as a contribution to the realization of quality education (SDGs 4). The method used is a literature study (library research) by reviewing various scientific sources through database searches such as Scopus and Google Scholar. Data were analyzed qualitatively using content analysis techniques to identify concepts, learning strategies, and the implications of causal thinking skills for quality education. The results of the study indicate that causal thinking skills are essential higher-order thinking skills in learning and are relevant to 21st-century global competencies. Various history learning strategies to support causal thinking skills include a narrative dialogic approach, inquiry-based learning, diverse learning techniques, the use of collaborative concept maps, and technology integration in learning. These findings confirm that strengthening causal thinking contributes to the achievement of SDGs 4 in developing critical, reflective, and responsible students for sustainability. Theoretically, this study strengthens the position of history learning as a vehicle for developing higher-order thinking competencies, while practically providing implications for educators and curriculum developers to direct history learning from a fact-oriented orientation to strengthening causal thinking competencies.